Specific Expression of Anaplasma marginale Major Surface Protein 2 Salivary Gland Variants Occurs in the Midgut and Is an Early Event during Tick Transmission - Löhr, Christiane V. (American Society for Microbiology, 2002)
Infectivity of Anaplasma spp. develops when infected ticks feed on a mammalian host (transmission feed). Specific Anaplasma marginale major surface protein 2 (MSP2) variants are selected for within the tick and are expressed within the salivary glands. The aims of this study were to determine when and where MSP2 variant selection occurs in the tick, how MSP2 expression is regulated in salivary glands of transmission-feeding ticks, and whether the number of A. marginale organisms per salivary gland is significantly increased during transmission feeding. The South Idaho strain of A. marginale was used, as MSP2 expression is restricted to two variants, SGV1 and SGV2, in Dermacentor andersoni. Using Western blot, real-time PCR, and DNA sequencing analyses it was shown that restriction and expression of MSP2 occurs early in the midgut within the first 48 h of the blood meal, when ticks acquire infection. A. marginale is present in the tick salivary glands before transmission feeding is initiated, but the msp2 mRNA and MSP2 protein levels per A. marginale organism increase only minimally and transiently in salivary glands of transmission-feeding ticks compared to that of unfed ticks. A. marginale numbers per tick increase gradually in salivary glands of both transmission-fed and unfed ticks. It is concluded that MSP2 variant selection is an early event in the tick and that MSP2 variants SGV1 and SGV2 are expressed both in the midgut and salivary glands. While MSP2 may be required for infectivity, there is no strict temporal correlation between MSP2 expression and the development of infectivity.